2011
DOI: 10.1371/journal.pone.0022399
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Expression of BORIS/CTCFL in Normal and Cancer Cells

Abstract: BORIS (CTCFL) is the paralog of CTCF (CCCTC-binding factor; NM_006565), a ubiquitously expressed DNA-binding protein with diverse roles in gene expression and chromatin organisation. BORIS and CTCF have virtually identical zinc finger domains, yet display major differences in their respective C- and N-terminal regions. Unlike CTCF, BORIS expression has been reported only in the testis and certain malignancies, leading to its classification as a “cancer-testis” antigen. However, the expression pattern of BORIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…BORIS expression has also been examined in the normal cervix and the HeLa cervical adenocarcinoma cell line (Renaud et al, 2011;Jones et al, 2011) but not in LSIL, HSIL, or ICC. In our study, expression of BORIS mRNA was observed in 12.7% of the samples analyzed, with a higher proportion of positive samples in the ICC group than in the LSIL and HSIL groups (P < 0.0005).…”
Section: Discussionmentioning
confidence: 99%
“…BORIS expression has also been examined in the normal cervix and the HeLa cervical adenocarcinoma cell line (Renaud et al, 2011;Jones et al, 2011) but not in LSIL, HSIL, or ICC. In our study, expression of BORIS mRNA was observed in 12.7% of the samples analyzed, with a higher proportion of positive samples in the ICC group than in the LSIL and HSIL groups (P < 0.0005).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicated that the expression of BORIS is not dependent on the cancerous or non-cancerous nature of cells and tissue. For example, although BORIS has been classified as a CT antigen, but new findings in melanoma, ovarian, prostate, breast, head and neck squamous cell carcinomas, and bladder carcinomas [12,[15][16][17]46] have shown that BORIS expression may not directly correlate with tumorigenicity. These studies reported that Boris expression in primary melanomas (27%) is not as frequent as originally estimated for melanoma cell lines (90%) [17], and when measured quantitatively, levels in tumors were not statistically different from those in normal prostate, bladder, and ovarian tissues [15,16].…”
Section: Boris Expression In Cancer and Non-cancer Mouse Cellsmentioning
confidence: 99%
“…On the contrary, the expression of BORIS cannot be detected in some cancer cell lines or tumors [10,12,[15][16][17]45,46], and has also been detected in several mouse and human somatic tissues and non-cancerous cell lines [17,46,47]. This may point to the widespread expression of BORIS which is not restricted to cancerous cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Its expression has been detected in various cancers and cancer cell lines (D'Arcy et al, 2008;Hoffmann et al, 2006;Hong et al, 2005;Jones et al, 2011;Kholmanskikh et al, 2008;Looijenga et al, 2006;Renaud et al, 2007;Risinger et al, 2007;Smith et al, 2009;Ulaner et al, 2003a;Woloszynska-Read et al, 2007).…”
Section: New Player On the Scene -Borismentioning
confidence: 99%